Follow the Light: "Lumen Gloriae" and "Visio Dei" in the Works of Dante Alighieri and Marguerite dicta Porete - Acosta-García, Pablo (Eikón / Imago, 2014)
In this article we compare the language of light used by Dante Alighieri with the one used by his “heretical” contemporary Marguerite dicta Porete (†1310) to express the final contact- vision of God. We will analyze both authors’ use of the images of light, of the gradual ascent and of the knot, placing their books in the context of the theological doctrines concerning the visio Dei in the 14th century. This will allow us to posit the authors’ shared eschatological background based on the conception of God as a visible being who radiates his love and knowledge through the created universe. In conclusion, we will discuss the visual and narrative strategies these authors employed in order to express a relationship with the divine, focusing on the historical heterodox implications of the Commedia and the Mirouer.